Degradable medical liquid storage bag material and preparation method thereof
By using PBAT, PLA, PBS, and starch such as biological degradable materials, and through the method of modified PBS resin and starch, the existing biological thin film materials are susceptible to deformed or degraded in high temperature environments, significantly improved, significantly improved, significantly improved, significantly improved The mechanical performance, blocking performance and antibacterial performance of medical storage bag materials.
Patent Information
- Application Number
- CN202411627402.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-24
AI Technical Summary
Existing biofilm materials are prone to deform or degradation in high temperature environments, and are difficult to fully meet the requirements in certain specific applications such as high barrier properties and biocompatibility, especially in medical liquid storage bag materials. .
Bio -degradable materials such as PBAT, PLA, PBS, and starch can be used as raw materials. The method of modifying PBS resin and starch through the combination of mixed -piercing network structures, and improving the mechanical performance, blocking performance and antibacterial performance of the material.
The comprehensive properties of medical fluid storage bag materials are significantly improved, including mechanical properties, barrier properties and antibacterial properties, ensuring the biodegradation rate of the material in the natural environment and maintaining stable performance in high temperature environments.
Smart Images

Figure BDA0005135088630000141 
Figure BDA0005135088630000151 
Figure BDA0005135088630000152
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of degradable plastics, and in particular relates to a degradable medical liquid storage bag material and a preparation method thereof. Background Art
[0002] With the rapid development of biotechnology, especially its wide application in pharmaceutical, cell culture and biomedical fields, the demand for biofilm materials is growing. In recent years, disposable biofilm bags, such as liquid storage bags, liquid preparation bags and cell reaction bags, have become important consumables for biopharmaceutical companies. These film bags not only provide efficient and convenient operation methods in the production process, but also greatly reduce the risk of cross contamination and improve the safety and reliability of production. Especially in the field of biopharmaceuticals, the application of disposable biofilm bags has expanded from simple liquid storage to complex cell culture and bioreaction processes, providing strong support for large-scale production and research and development.
[0003] Green environmental protection is the focus of the current development of biofilm materials. Although traditional plastic film materials have good physical and chemical properties, they are difficult to degrade after use, causing serious pollution to the environment. Therefore, the development of degradable biofilm materials has become a hot topic of research. The commonly used biofilm materials in the prior art mainly include polylactic acid, polyurethane, polybutylene terephthalate-adipate, polybutylene succinate, polyurethane, starch, cellulose, etc., and each material has its own unique advantages and disadvantages. Polylactic acid is biodegradable, environmentally friendly, has good mechanical properties and transparency, and can be produced by microbial fermentation, but has poor heat resistance, is easily deformed at high temperatures, and has average barrier properties, especially in humid environments, with high costs and high processing difficulties. Polybutylene terephthalate-adipate and polybutylene succinate are biodegradable, environmentally friendly, have good flexibility and ductility, and have good processing properties, but have poor heat resistance, are easily deformed at high temperatures, have average barrier properties, and have high costs. Polyurethane has good mechanical properties and flexibility, good chemical stability and solvent resistance, good biocompatibility and biodegradability, but it is costly, difficult to process, sensitive to certain chemicals that may affect performance, and may suffer from incomplete degradation after long-term use.
[0004] By blending the above materials, the performance of a single material can be improved, such as improving mechanical strength, flexibility, chemical stability or heat resistance, but there are still some disadvantages. For example, the compatibility problem of different materials may increase the difficulty of processing, requiring special processing equipment and processes; simple blending often leads to limited improvement in material performance, especially heat resistance, which may deform or degrade in some high temperature environments, affecting performance; although blending can improve certain properties, it may still not fully meet the requirements in some specific applications, such as high barrier properties and biocompatibility. Therefore, it is urgent to provide a degradable medical liquid storage bag material with good mechanical properties, barrier properties and antibacterial properties. Summary of the invention
[0005] The purpose of the present invention is to provide a degradable medical liquid storage bag material, which uses biodegradable materials such as PBAT resin, PLA resin, PBS resin, starch, etc. as raw materials, is green and environmentally friendly, and effectively improves the mechanical properties, barrier properties and antibacterial properties of the liquid storage bag material by modifying the PBS resin and starch. The preparation method of the present invention is simple.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a degradable medical liquid storage bag material, comprising the following raw materials:
[0008] 40-60 parts by weight of PBAT resin, 20-40 parts by weight of PLA resin, 10-30 parts by weight of modified PBS resin, 2-8 parts by weight of modified starch, 1-3 parts by weight of plasticizer, and 1-2 parts by weight of lubricant.
[0009] The present invention uses PBAT (polybutylene terephthalate-adipate), PLA (polylactic acid), PBS (polybutylene succinate) and starch as raw materials to prepare a degradable medical liquid storage bag material, wherein PBAT and PBS have good flexibility and ductility, PLA provides excellent mechanical properties and biocompatibility, and starch increases the biodegradability of the material. These raw materials are blended to form an interpenetrating network structure, thereby improving the comprehensive performance of the material. The flexible segments of PBAT and PBS complement the rigid segments of PLA, thereby enhancing the mechanical properties and processing properties of the material. At the same time, the presence of starch promotes the microbial degradation of the material, thereby ensuring the biodegradation rate of the material in the natural environment.
[0010] Preferably, the preparation method of the modified PBS resin comprises the following steps:
[0011] 10-20 parts by weight of zirconium nitrate is added to 80-90 parts by weight of nitric acid aqueous solution and ultrasonicated for 5-15 minutes, then 2-5 parts by weight of tantalum pentachloride is added and reacted for 15-20 hours, centrifuged, washed, dried, and calcined for 1-3 hours to obtain tantalum-doped zirconium dioxide nanosheets;
[0012] Add 2-4 parts by weight of tantalum-doped zirconium dioxide nanosheets to 50-70 parts by weight of water and stir for 10-30 minutes, then add 0.3-0.6 parts by weight of dodecyl dimethyl ethyl ammonium bromide and continue stirring for 30-50 minutes, centrifuge, wash, and dry to obtain modified tantalum-doped zirconium dioxide nanosheets;
[0013] 90-100 parts by weight of PBS resin, 2-8 parts by weight of modified tantalum-doped zirconium dioxide nanosheets and 0.4-0.6 parts by weight of zinc stearate are added into a high-speed mixer for mixing, and then added into a twin-screw extruder for extrusion granulation to obtain modified PBS resin.
[0014] The present invention uses modified tantalum-doped zirconium dioxide nanosheets to blend and modify PBS resin, further improving the barrier properties of medical liquid storage bag materials. The present invention uses a hydrothermal method to obtain tantalum-doped zirconium dioxide nanosheets, and then uses dodecyl dimethyl ethyl ammonium bromide for surface treatment, which can be adsorbed on the surface of the tantalum-doped zirconium dioxide nanosheets to form a hydrophobic film, which not only enhances the dispersibility and stability of the nanosheets, but also improves its compatibility with the PBS resin matrix. The modified tantalum-doped zirconium dioxide nanosheets have a high specific surface area and active sites, and can form a microscopic dense protective layer inside the matrix material, thereby significantly improving the barrier properties and heat resistance of the material. First, the tantalum-doped zirconium dioxide nanosheets prepared by the hydrothermal method have the characteristics of being highly dispersed and stable. These nanosheets can be evenly distributed in the matrix material to form a continuous nanoscale protective layer, effectively preventing the penetration of gas and moisture, thereby significantly improving the barrier properties of the composite material. Secondly, dodecyldimethylethylammonium bromide, as a cationic surfactant, can be effectively adsorbed on the surface of tantalum-doped zirconium dioxide nanosheets to form a hydrophobic film, which not only enhances the dispersibility and stability of the nanosheets, but also improves its compatibility with the PBS resin matrix, allowing the nanosheets to be better dispersed in the matrix material to form a uniform microstructure, further improving the mechanical properties and barrier properties of the composite material.
[0015] Furthermore, the preparation method of the modified PBS resin comprises the following steps:
[0016] 10-20 parts by weight of zirconium nitrate are added to 80-90 parts by weight of 20-30wt% nitric acid aqueous solution, and ultrasonicated for 5-15 minutes, and then 2-5 parts by weight of tantalum pentachloride are added, and the pH value is adjusted to 8-10, and the reaction is carried out at 150-170°C and 60-100rpm for 15-20 hours, centrifuged, washed, dried, and then calcined at 400-500°C for 1-3 hours to obtain tantalum-doped zirconium dioxide nanosheets; wherein the frequency of the ultrasound is 20-30kHz and the power is 100-200W;
[0017] 2-4 parts by weight of tantalum-doped zirconium dioxide nanosheets are added to 50-70 parts by weight of water, stirred at 75-80° C. and 60-100 rpm for 10-30 minutes, then 0.3-0.6 parts by weight of dodecyl dimethyl ethyl ammonium bromide are added and stirred for 30-50 minutes, centrifuged, washed, and dried to obtain modified tantalum-doped zirconium dioxide nanosheets;
[0018] 90-100 parts by weight of PBS resin, 2-8 parts by weight of modified tantalum-doped zirconium dioxide nanosheets and 0.4-0.6 parts by weight of zinc stearate are added into a high-speed mixer, mixed at a speed of 300-500 rpm for 10-30 minutes, and then added into a twin-screw extruder for extrusion granulation. The extrusion temperatures are: 100-110° C. in the feeding section, 110-120° C. in the melting section, 130-140° C. in the homogenizing section, 120-130° C. in the die head, and 100-200 rpm in the screw speed, to obtain a modified PBS resin.
[0019] Preferably, the method for preparing the modified starch comprises the following steps:
[0020] 10-15 parts by weight of pea starch is added to 80-120 parts by weight of water and ultrasonicated for 5-15 minutes, then 0.1-0.3 parts by weight of complex enzyme is added for enzymolysis for 5-8 hours, centrifuged, washed, and dried to obtain microporous starch;
[0021] 7-10 parts by weight of microporous starch is added to 80-100 parts by weight of ethanol aqueous solution and ultrasonicated for 20-30 minutes, then 3-5 parts by weight of potassium hydroxide is added and stirred for 0.5-1.5 hours, then 8-12 parts by weight of monochloroacetic acid is added and stirred for 2-4 hours, centrifuged, washed, and dried to obtain carboxymethylated microporous starch;
[0022] 3-5 parts by weight of carboxymethylated microporous starch are added to 40-60 parts by weight of water and stirred for 40-50 minutes, and then 0.3-0.6 parts by weight of tea polyphenols, 0.2-0.4 parts by weight of choline chloride and 0.05-0.08 parts by weight of sodium persulfate are added and stirred for 4-6 hours, centrifuged, washed and dried to obtain modified starch.
[0023] The invention selects pea starch as a raw material, firstly uses a composite enzyme composed of alpha-amylase and pullulanase for enzymolysis to obtain microporous starch, then performs carboxymethylation treatment, and finally reacts with tea polyphenols, choline chloride and sodium persulfate to obtain modified starch with antibacterial performance. The invention can not only make the medical liquid storage bag material have excellent and stable antibacterial performance, but also avoid the influence of directly adding antibacterial agents on the mechanical properties of the material.
[0024] First, through the combined enzymatic hydrolysis of α-amylase and pullulanase, the amylose and amylopectin in pea starch are partially degraded, so that a large number of micropores are formed inside the starch granules, which increases the specific surface area and active sites of the starch. These microporous structures not only improve the solubility and reactivity of the starch, but also provide more binding sites for subsequent chemical modifications; then, through carboxymethylation treatment, part of the hydroxyl groups in the microporous starch are replaced by carboxymethyl groups, which not only improves the film-forming property of the starch, but also enhances the electrostatic repulsion between starch molecules, further improving the dispersibility and stability of the starch; finally, the carboxymethylated starch is reacted with tea polyphenols, choline chloride, and sodium persulfate to prepare a polysaccharide having antibacterial properties. The modified starch has good performance. Tea polyphenols are a natural polyphenol compound with good antibacterial properties and can effectively inhibit the growth of various bacteria and fungi. Choline chloride can introduce quaternary ammonium salt antibacterial structure into starch molecules, which can destroy the integrity of bacterial cell membranes and cause bacterial death. Sodium persulfate can trigger free radical polymerization reaction, promote the uniform dispersion and fixation of tea polyphenols and choline chloride on the carboxymethylated starch substrate, and form a stable antibacterial network structure. The above modified antibacterial components are not only uniformly dispersed in the starch substrate, but also form stable chemical bonds with starch molecules, avoiding the loss of antibacterial components during processing and use, thereby ensuring the long-term antibacterial performance of the liquid storage bag material. In addition, since the antibacterial components are fixed in the starch substrate by chemical bonding, they will not affect the mechanical properties of the material like the traditional direct addition of antibacterial agents, ensuring that the modified starch has excellent mechanical properties in the application of medical liquid storage bag materials.
[0025] Furthermore, the preparation method of the modified starch comprises the following steps:
[0026] Add 10-15 parts by weight of pea starch to 80-120 parts by weight of water and ultrasonicate for 5-15 minutes, adjust the pH value to 4-6, then add 0.1-0.3 parts by weight of complex enzyme, perform enzymolysis at 40-50°C and 60-100rpm for 5-8 hours, centrifuge, wash, and dry to obtain microporous starch; wherein the frequency of the ultrasound is 20-30kHz and the power is 100-200W;
[0027] 7-10 parts by weight of microporous starch is added to 80-100 parts by weight of 70-85wt% ethanol aqueous solution, and ultrasonicated for 20-30 minutes, and then 3-5 parts by weight of potassium hydroxide is added, and stirred for 0.5-1.5 hours at 25-30°C and 60-100rpm, and then 8-12 parts by weight of monochloroacetic acid is added, and stirred for 2-4 hours at 45-50°C and 60-100rpm, and centrifuged, washed, and dried to obtain carboxymethylated microporous starch; wherein the frequency of the ultrasound is 20-30kHz and the power is 100-200W;
[0028] 3-5 parts by weight of carboxymethylated microporous starch are added to 40-60 parts by weight of water, stirred at 50-55° C. and 60-100 rpm for 40-50 min, then 0.3-0.6 parts by weight of tea polyphenols, 0.2-0.4 parts by weight of choline chloride, and 0.05-0.08 parts by weight of sodium persulfate are added, and stirring is continued for 4-6 hours, centrifuged, washed, and dried to obtain modified starch.
[0029] Preferably, the complex enzyme consists of α-amylase and pullulanase in a weight ratio of 3-5:1.
[0030] Preferably, the plasticizer is one or more of triethyl citrate, acetyl triethyl citrate, tributyl citrate, acetyl tributyl citrate, glycidyl methacrylate, and dibutyl phthalate.
[0031] Furthermore, the plasticizer is triethyl acetyl citrate.
[0032] Preferably, the lubricant is one or more of oleamide, stearamide, ethylene bisstearamide, pentaerythritol stearate, and glyceryl monostearate.
[0033] Furthermore, the lubricant is composed of oleic acid amide and pentaerythritol stearate in a weight ratio of 1:2-4.
[0034] The present invention provides a method for preparing a degradable medical liquid storage bag material, comprising the following steps:
[0035] PBAT resin, PLA resin, modified PBS resin, modified starch, plasticizer, and lubricant are weighed and added into a high-speed mixer, and mixed at a speed of 300-400 rpm for 5-15 minutes to obtain a premix, and the premix is added into a twin-screw extruder for extrusion granulation to obtain the degradable medical liquid storage bag material.
[0036] Preferably, the extrusion temperature is: 150-160°C in the feeding section, 170-180°C in the melting section, 180-190°C in the homogenizing section, 170-180°C in the die head temperature; and the screw speed is 100-150rpm.
[0037] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0038] 1. The present invention provides a method for preparing a degradable medical liquid storage bag material. PBAT, PLA, PBS and starch are used as raw materials. An interpenetrating network structure is formed by blending, thereby improving the comprehensive performance of the material. The flexible segments of PBAT and PBS complement the rigid segments of PLA, thereby enhancing the mechanical properties and processing properties of the material. At the same time, the presence of starch promotes the microbial degradation of the material, thereby ensuring the biodegradation rate of the material in the natural environment.
[0039] 2. In the present invention, modified tantalum-doped zirconium dioxide nanosheets are used to blend and modify PBS resin, thereby further improving the barrier properties of the medical liquid storage bag material. The modified tantalum-doped zirconium dioxide nanosheets have a high specific surface area and active sites, and can form a microscopic dense protective layer inside the matrix material, thereby significantly improving the barrier properties and heat resistance of the material. At the same time, dodecyl dimethyl ethyl ammonium bromide is adsorbed on the surface of tantalum-doped zirconium dioxide nanosheets to form a hydrophobic film, which not only enhances the dispersibility and stability of the nanosheets, but also improves its compatibility with the PBS resin matrix, so that the nanosheets can be better dispersed in the matrix material to form a uniform microstructure, further improving the mechanical properties and barrier properties of the composite material.
[0040] 3. The present invention partially degrades the amylose and amylopectin in pea starch through the composite enzymatic hydrolysis of α-amylase and pullulanase, thereby forming a large number of micropores inside the starch granules, increasing the specific surface area and active sites of the starch, and replacing part of the hydroxyl groups in the microporous starch with carboxymethyl groups through carboxymethylation treatment, which not only improves the film-forming property of the starch, but also enhances the electrostatic repulsion between starch molecules, further improving the dispersibility and stability of the starch; the modified starch with antibacterial properties is obtained by reacting the carboxymethylated starch with tea polyphenols, choline chloride and sodium persulfate, wherein the antibacterial components are not only uniformly dispersed in the starch substrate, but also form stable chemical bonds with the starch molecules, thereby avoiding the loss of the antibacterial components during processing and use, thereby ensuring the long-term antibacterial properties of the liquid storage bag material. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] PBAT resin, brand: ECO-A20, melt index is 20g / 10min (190℃, 2.16kg, ISO1133), manufacturer: Changchun Company, Taiwan, China.
[0043] PBS resin, brand: FZ91PB, melt index is 5g / 10min (190℃, 2.16kg, ISO1133), manufacturer: PTT Company of Thailand.
[0044] PLA resin, brand: V554X51, melt index is 6g / 10min (190℃, 2.16kg, ISO1133), manufacturer: Toray Industries, Japan.
[0045] Pea starch, No.: GC33612, Manufacturer: Shanghai Guchen Biotechnology Co., Ltd.
[0046] Example 1
[0047] This embodiment provides a degradable medical liquid storage bag material, comprising the following raw materials in parts by weight:
[0048] 50 parts by weight of PBAT resin, 30 parts by weight of PLA resin, 20 parts by weight of modified PBS resin, 5 parts by weight of modified starch, 2.5 parts by weight of plasticizer, and 1.5 parts by weight of lubricant.
[0049] The plasticizer is triethyl acetyl citrate.
[0050] The lubricant is composed of oleic acid amide and pentaerythritol stearate in a weight ratio of 1:3.
[0051] The preparation method of the modified PBS resin comprises the following steps:
[0052] 15 parts by weight of zirconium nitrate are added to 85 parts by weight of 25wt% nitric acid aqueous solution and ultrasonicated for 10 minutes, then 3.5 parts by weight of tantalum pentachloride are added, the pH value is adjusted to 9.5, the reaction is carried out at 160°C and 80rpm for 18 hours, centrifuged, washed, dried, and then calcined at 450°C for 2 hours to obtain tantalum-doped zirconium dioxide nanosheets; wherein the frequency of the ultrasound is 20kHz and the power is 150W;
[0053] 3 parts by weight of tantalum-doped zirconium dioxide nanosheets were added to 60 parts by weight of water, stirred at 78° C. and 80 rpm for 20 minutes, then 0.5 parts by weight of dodecyl dimethyl ethyl ammonium bromide was added and stirred for 40 minutes, centrifuged, washed, and dried to obtain modified tantalum-doped zirconium dioxide nanosheets;
[0054] 95 parts by weight of PBS resin, 5 parts by weight of modified tantalum-doped zirconium dioxide nanosheets, and 0.5 parts by weight of zinc stearate were added into a high-speed mixer, mixed at 400 rpm for 20 min, and then added into a twin-screw extruder for extrusion granulation. The extrusion temperatures were: 100°C in the feeding section, 120°C in the melting section, 130°C in the homogenizing section, 120°C in the die head temperature, and 150 rpm in the screw speed to obtain a modified PBS resin.
[0055] The preparation method of the modified starch comprises the following steps:
[0056] 12 parts by weight of pea starch are added to 100 parts by weight of water, and ultrasonicated for 10 minutes, the pH value is adjusted to 5, and then 0.15 parts by weight of composite enzyme is added, and enzymolysis is carried out at 42° C. and 80 rpm for 6 hours, centrifuged, washed, and dried to obtain microporous starch; the composite enzyme is composed of α-amylase and pullulanase in a weight ratio of 4:1; the enzyme activity of the α-amylase is 4000u / g, and the enzyme activity of the pullulanase is 2000u / g; wherein the frequency of the ultrasound is 20kHz and the power is 150W;
[0057] 8.5 parts by weight of microporous starch are added to 90 parts by weight of 80wt% ethanol aqueous solution, and ultrasonicated for 25 minutes, and then 4.5 parts by weight of potassium hydroxide are added, and stirred for 1 hour at 27°C and 80rpm, and then 10 parts by weight of monochloroacetic acid are added, and stirred for 3 hours at 46°C and 80rpm, and centrifuged, washed, and dried to obtain carboxymethylated microporous starch; wherein the frequency of the ultrasound is 20kHz and the power is 150W;
[0058] 4 parts by weight of carboxymethylated microporous starch were added to 50 parts by weight of water, stirred at 53°C and 80 rpm for 45 minutes, then 0.5 parts by weight of tea polyphenols, 0.3 parts by weight of choline chloride and 0.06 parts by weight of sodium persulfate were added and stirred for 5 hours, centrifuged, washed and dried to obtain modified starch.
[0059] This embodiment provides a method for preparing a degradable medical liquid storage bag material, comprising the following steps:
[0060] Weigh PBAT resin, PLA resin, modified PBS resin, modified starch, plasticizer, and lubricant, add them into a high-speed mixer, mix them at 350 rpm for 10 min to obtain a premix, add the premix into a twin-screw extruder for extrusion granulation, the extrusion temperature is: 150°C in the feeding section, 170°C in the melting section, 190°C in the homogenizing section, 180°C in the die head temperature, and the screw speed is 120 rpm to obtain the degradable medical liquid storage bag material.
[0061] Example 2
[0062] This embodiment provides a degradable medical liquid storage bag material, comprising the following raw materials in parts by weight:
[0063] 40 parts by weight of PBAT resin, 20 parts by weight of PLA resin, 10 parts by weight of modified PBS resin, 2 parts by weight of modified starch, 1 part by weight of plasticizer, and 1 part by weight of lubricant.
[0064] The plasticizer is triethyl acetyl citrate.
[0065] The lubricant is composed of oleic acid amide and pentaerythritol stearate in a weight ratio of 1:2.
[0066] The preparation method of the modified PBS resin is the same as that in Example 1.
[0067] The preparation method of the modified starch is the same as that in Example 1.
[0068] This embodiment provides a method for preparing a degradable medical liquid storage bag material, comprising the following steps:
[0069] Weigh PBAT resin, PLA resin, modified PBS resin, modified starch, plasticizer, and lubricant, add them into a high-speed mixer, mix them at 300 rpm for 5 minutes to obtain a premix, add the premix into a twin-screw extruder for extrusion granulation, the extrusion temperature is: 150°C in the feeding section, 170°C in the melting section, 180°C in the homogenizing section, 170°C in the die head temperature, and 100 rpm in the screw speed to obtain the degradable medical liquid storage bag material.
[0070] Example 3
[0071] This embodiment provides a degradable medical liquid storage bag material, comprising the following raw materials in parts by weight:
[0072] 60 parts by weight of PBAT resin, 40 parts by weight of PLA resin, 30 parts by weight of modified PBS resin, 8 parts by weight of modified starch, 3 parts by weight of plasticizer, and 2 parts by weight of lubricant.
[0073] The plasticizer is triethyl acetyl citrate.
[0074] The lubricant is composed of oleic acid amide and pentaerythritol stearate in a weight ratio of 1:4.
[0075] The preparation method of the modified PBS resin is the same as that in Example 1.
[0076] The preparation method of the modified starch is the same as that in Example 1.
[0077] This embodiment provides a method for preparing a degradable medical liquid storage bag material, comprising the following steps:
[0078] Weigh PBAT resin, PLA resin, modified PBS resin, modified starch, plasticizer, and lubricant, add them into a high-speed mixer, mix them at 400 rpm for 15 minutes to obtain a premix, add the premix into a twin-screw extruder for extrusion granulation, the extrusion temperature is: 160°C in the feeding section, 180°C in the melting section, 190°C in the homogenizing section, 180°C in the die head temperature, and 150 rpm in the screw speed to obtain the degradable medical liquid storage bag material.
[0079] Comparative Example 1
[0080] The difference between this comparative example and Example 1 is that the preparation method of the modified PBS resin is different, specifically as follows: the preparation method of the modified PBS resin comprises the following steps:
[0081] 95 parts by weight of PBS resin, 5 parts by weight of zirconium dioxide (commercially available), and 0.5 parts by weight of zinc stearate were added into a high-speed mixer, mixed at a speed of 400 rpm for 20 min, and then added into a twin-screw extruder for extrusion granulation. The extrusion temperatures were: 100° C. in the feeding section, 120° C. in the melting section, 130° C. in the homogenizing section, 120° C. in the die head temperature, and 150 rpm in the screw speed, to obtain a modified PBS resin.
[0082] Comparative Example 2
[0083] The difference between this comparative example and Example 1 is that the preparation method of the modified PBS resin is different, specifically as follows: the preparation method of the modified PBS resin comprises the following steps:
[0084] 15 parts by weight of zirconium nitrate are added to 85 parts by weight of 25wt% nitric acid aqueous solution and ultrasonicated for 10 minutes, then 3.5 parts by weight of tantalum pentachloride are added, the pH value is adjusted to 9.5, the reaction is carried out at 160°C and 80rpm for 18 hours, centrifuged, washed, dried, and then calcined at 450°C for 2 hours to obtain tantalum-doped zirconium dioxide nanosheets; wherein the frequency of the ultrasound is 20kHz and the power is 150W;
[0085] 95 parts by weight of PBS resin, 5 parts by weight of tantalum-doped zirconium dioxide nanosheets, and 0.5 parts by weight of zinc stearate were added into a high-speed mixer, mixed at 400 rpm for 20 min, and then added into a twin-screw extruder for extrusion granulation. The extrusion temperatures were: 100°C in the feeding section, 120°C in the melting section, 130°C in the homogenizing section, 120°C in the die head temperature, and 150 rpm in the screw speed to obtain a modified PBS resin.
[0086] Comparative Example 3
[0087] The difference between this comparative example and Example 1 is that the modified PBS resin is replaced by PBS resin.
[0088] Comparative Example 4
[0089] The difference between this comparative example and Example 1 is that the preparation method of the modified starch is different, specifically as follows: the preparation method of the modified starch comprises the following steps:
[0090] 8.5 parts by weight of pea starch are added to 90 parts by weight of 80 wt% ethanol aqueous solution, and the mixture is ultrasonicated for 25 minutes. Then, 4.5 parts by weight of potassium hydroxide are added, and the mixture is stirred at 27° C. and 80 rpm for 1 hour. Then, 10 parts by weight of monochloroacetic acid are added, and the mixture is stirred at 46° C. and 80 rpm for 3 hours. The mixture is centrifuged, washed, and dried to obtain carboxymethylated starch. The ultrasonic frequency is 20 kHz and the power is 150 W.
[0091] 4 parts by weight of carboxymethylated starch were added to 50 parts by weight of water, stirred at 53° C. and 80 rpm for 45 min, then 0.5 parts by weight of tea polyphenols, 0.3 parts by weight of choline chloride and 0.06 parts by weight of sodium persulfate were added, and stirring was continued for 5 h. The mixture was centrifuged, washed and dried to obtain modified starch.
[0092] Comparative Example 5
[0093] The difference between this comparative example and Example 1 is that the preparation method of the modified starch is different, specifically as follows: the preparation method of the modified starch comprises the following steps:
[0094] 12 parts by weight of pea starch are added to 100 parts by weight of water, and ultrasonicated for 10 minutes, the pH value is adjusted to 5, and then 0.15 parts by weight of composite enzyme is added, and enzymolysis is carried out at 42° C. and 80 rpm for 6 hours, centrifuged, washed, and dried to obtain microporous starch; the composite enzyme is composed of α-amylase and pullulanase in a weight ratio of 4:1; the enzyme activity of the α-amylase is 4000u / g, and the enzyme activity of the pullulanase is 2000u / g; wherein the frequency of the ultrasound is 20kHz and the power is 150W;
[0095] 8.5 parts by weight of microporous starch are added to 90 parts by weight of 80wt% ethanol aqueous solution, and ultrasonicated for 25 minutes, and then 4.5 parts by weight of potassium hydroxide are added, and stirred for 1 hour at 27°C and 80rpm, and then 10 parts by weight of monochloroacetic acid are added, and stirred for 3 hours at 46°C and 80rpm, and centrifuged, washed, and dried to obtain carboxymethylated microporous starch; wherein the frequency of the ultrasound is 20kHz and the power is 150W;
[0096] 4 parts by weight of carboxymethylated microporous starch were added to 50 parts by weight of water, stirred at 53°C and 80 rpm for 45 minutes, then 0.8 parts by weight of tea polyphenols and 0.06 parts by weight of sodium persulfate were added, stirred for 5 hours, centrifuged, washed, and dried to obtain modified starch.
[0097] Comparative Example 6
[0098] The difference between this comparative example and Example 1 is that the preparation method of the modified starch is different, specifically as follows: the preparation method of the modified starch comprises the following steps:
[0099] 12 parts by weight of pea starch are added to 100 parts by weight of water, and ultrasonicated for 10 minutes, the pH value is adjusted to 5, and then 0.15 parts by weight of composite enzyme is added, and enzymolysis is carried out at 42° C. and 80 rpm for 6 hours, centrifuged, washed, and dried to obtain microporous starch; the composite enzyme is composed of α-amylase and pullulanase in a weight ratio of 4:1; the enzyme activity of the α-amylase is 4000u / g, and the enzyme activity of the pullulanase is 2000u / g; wherein the frequency of the ultrasound is 20kHz and the power is 150W;
[0100] 8.5 parts by weight of microporous starch are added to 90 parts by weight of 80wt% ethanol aqueous solution, and ultrasonicated for 25 minutes, and then 4.5 parts by weight of potassium hydroxide are added, and stirred for 1 hour at 27°C and 80rpm, and then 10 parts by weight of monochloroacetic acid are added, and stirred for 3 hours at 46°C and 80rpm, and centrifuged, washed, and dried to obtain carboxymethylated microporous starch; wherein the frequency of the ultrasound is 20kHz and the power is 150W;
[0101] 4 parts by weight of carboxymethylated microporous starch were added to 50 parts by weight of water, stirred at 53° C. and 80 rpm for 45 minutes, then 0.8 parts by weight of choline chloride and 0.06 parts by weight of sodium persulfate were added, and stirring was continued for 5 hours. The mixture was centrifuged, washed, and dried to obtain modified starch.
[0102] Performance Testing
[0103] 1. The tensile strength of the above Examples 1-3 and Comparative Examples 1-6 was measured according to the standard GB / T1040.3-2006; the relative biodegradation rate (180 days) was measured according to the standard GB / T19277.1-2011; the results are shown in Table 1.
[0104] Table 1: Mechanical properties and degradation performance test results
[0105]
[0106]
[0107] 2. The water vapor transmission rates of the above Examples 1-3 and Comparative Examples 1-3 were measured according to the standard GB / T 1037-2021; the oxygen transmission rates were measured according to the standard GB / T31354-2014; the results are shown in Table 2.
[0108] Table 2: Barrier performance test results
[0109]
[0110] 3. The antibacterial rates of Examples 1-3 and Comparative Examples 4-6 were determined according to the standard GB / T 31402-2023. The test bacteria were Escherichia coli (ATCC 8739) and Staphylococcus aureus (ATCC 6538P). The results are shown in Table 3.
[0111] Table 3: Antibacterial performance test results
[0112]
[0113]
[0114] It can be seen from the above performance test results that the degradable medical liquid storage bag materials prepared in Examples 1-3 have excellent mechanical properties, biodegradable properties, barrier properties and antibacterial properties, especially the comprehensive performance of the liquid storage bag material in Example 1 is the most outstanding. This is because the present invention significantly improves the barrier properties and thermal stability of the material by blending and modifying the PBS resin with tantalum-doped zirconium dioxide nanosheets, and at the same time performs antibacterial modification on the starch, so that the antibacterial components are uniformly dispersed in the starch substrate and form stable chemical bonds with the starch molecules, ensuring that the antibacterial components are stably dispersed in the matrix material without migration, thereby making the liquid storage bag material have stable antibacterial properties and good mechanical properties.
[0115] In comparison, since Comparative Examples 1-6 did not adopt the necessary technical solutions, the corresponding performance tests were significantly worse than those of Examples 1-3. In Comparative Examples 1-3, the modified PBS resin was not prepared by a specific method, and in Comparative Examples 4-6, the modified starch with antibacterial effect was not used. It can be seen from the results that the barrier properties and antibacterial properties of the liquid storage bag materials were reduced. The above experimental results further prove the importance of the technical solutions defined in the present invention for its technical effects.
[0116] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A degradable medical liquid storage bag material, characterized in that: It includes the following raw materials in parts by weight: 40-60 parts by weight of PBAT resin, 20-40 parts by weight of PLA resin, 10-30 parts by weight of modified PBS resin, 2-8 parts by weight of modified starch, 1-3 parts by weight of plasticizer, and 1-2 parts by weight of lubricant; the modified PBS resin consists of PBS resin, modified tantalum-doped zirconium dioxide nanosheets and zinc stearate.
2. The degradable medical liquid storage bag material according to claim 1, characterized in that: The preparation method of the modified PBS resin comprises the following steps: 10-20 parts by weight of zirconium nitrate is added to 80-90 parts by weight of nitric acid aqueous solution and ultrasonicated for 5-15 minutes, then 2-5 parts by weight of tantalum pentachloride is added and reacted for 15-20 hours, centrifuged, washed, dried, and calcined for 1-3 hours to obtain tantalum-doped zirconium dioxide nanosheets; Add 2-4 parts by weight of tantalum-doped zirconium dioxide nanosheets to 50-70 parts by weight of water and stir for 10-30 minutes, then add 0.3-0.6 parts by weight of dodecyl dimethyl ethyl ammonium bromide and continue stirring for 30-50 minutes, centrifuge, wash, and dry to obtain modified tantalum-doped zirconium dioxide nanosheets; 90-100 parts by weight of PBS resin, 2-8 parts by weight of modified tantalum-doped zirconium dioxide nanosheets and 0.4-0.6 parts by weight of zinc stearate are added into a high-speed mixer for mixing, and then added into a twin-screw extruder for extrusion granulation to obtain modified PBS resin.
3. The degradable medical liquid storage bag material according to claim 2, characterized in that: The preparation method of the modified PBS resin comprises the following steps: 10-20 parts by weight of zirconium nitrate is added to 80-90 parts by weight of 20-30wt% nitric acid aqueous solution, and ultrasonicated for 5-15 minutes, and then 2-5 parts by weight of tantalum pentachloride is added, the pH value is adjusted to 8-10, and the reaction is carried out at 150-170°C and 60-100 rpm for 15-20 hours, centrifuged, washed, dried, and then calcined at 400-500°C for 1-3 hours to obtain tantalum-doped zirconium dioxide nanosheets; 2-4 parts by weight of tantalum-doped zirconium dioxide nanosheets are added to 50-70 parts by weight of water, stirred at 75-80° C. and 60-100 rpm for 10-30 minutes, then 0.3-0.6 parts by weight of dodecyl dimethyl ethyl ammonium bromide are added and stirred for 30-50 minutes, centrifuged, washed, and dried to obtain modified tantalum-doped zirconium dioxide nanosheets; 90-100 parts by weight of PBS resin, 2-8 parts by weight of modified tantalum-doped zirconium dioxide nanosheets, and 0.4-0.6 parts by weight of zinc stearate are added into a high-speed mixer, mixed at a speed of 300-500 rpm for 10-30 minutes, and then added into a twin-screw extruder for extrusion granulation to obtain a modified PBS resin.
4. The degradable medical liquid storage bag material according to claim 1, characterized in that: The preparation method of the modified starch comprises the following steps: 10-15 parts by weight of pea starch is added to 80-120 parts by weight of water and ultrasonicated for 5-15 minutes, then 0.1-0.3 parts by weight of complex enzyme is added for enzymolysis for 5-8 hours, centrifuged, washed, and dried to obtain microporous starch; 7-10 parts by weight of microporous starch is added to 80-100 parts by weight of ethanol aqueous solution and ultrasonicated for 20-30 minutes, then 3-5 parts by weight of potassium hydroxide is added and stirred for 0.5-1.5 hours, then 8-12 parts by weight of monochloroacetic acid is added and stirred for 2-4 hours, centrifuged, washed, and dried to obtain carboxymethylated microporous starch; 3-5 parts by weight of carboxymethylated microporous starch are added to 40-60 parts by weight of water and stirred for 40-50 minutes, and then 0.3-0.6 parts by weight of tea polyphenols, 0.2-0.4 parts by weight of choline chloride and 0.05-0.08 parts by weight of sodium persulfate are added and stirred for 4-6 hours, centrifuged, washed and dried to obtain modified starch.
5. The degradable medical liquid storage bag material according to claim 4, characterized in that: The preparation method of the modified starch comprises the following steps: 10-15 parts by weight of pea starch is added to 80-120 parts by weight of water, ultrasonicated for 5-15 minutes, the pH value is adjusted to 4-6, and then 0.1-0.3 parts by weight of complex enzyme is added, enzymolysis is carried out at 40-50° C. and 60-100 rpm for 5-8 hours, centrifuged, washed, and dried to obtain microporous starch; 7-10 parts by weight of microporous starch is added to 80-100 parts by weight of 70-85wt% ethanol aqueous solution, and ultrasonicated for 20-30 minutes, and then 3-5 parts by weight of potassium hydroxide is added and stirred at 25-30°C and 60-100rpm for 0.5-1.5h, and then 8-12 parts by weight of monochloroacetic acid is added and stirred at 45-50°C and 60-100rpm for 2-4h, centrifuged, washed, and dried to obtain carboxymethylated microporous starch; 3-5 parts by weight of carboxymethylated microporous starch are added to 40-60 parts by weight of water, stirred at 50-55° C. and 60-100 rpm for 40-50 min, then 0.3-0.6 parts by weight of tea polyphenols, 0.2-0.4 parts by weight of choline chloride, and 0.05-0.08 parts by weight of sodium persulfate are added, and stirring is continued for 4-6 hours, centrifuged, washed, and dried to obtain modified starch.
6. The degradable medical liquid storage bag material according to claim 4, characterized in that: The complex enzyme consists of alpha-amylase and pullulanase.
7. The degradable medical liquid storage bag material according to claim 1, characterized in that: The plasticizer is one or more of triethyl citrate, triethyl acetyl citrate, tributyl citrate, tributyl acetyl citrate, glycidyl methacrylate, and dibutyl phthalate.
8. The degradable medical liquid storage bag material according to claim 1, characterized in that: The lubricant is one or more of oleic acid amide, stearic acid amide, ethylene bis stearic acid amide, pentaerythritol stearate, and glyceryl monostearate.
9. The degradable medical liquid storage bag material according to claim 8, characterized in that: The lubricant is composed of oleic acid amide and pentaerythritol stearate in a weight ratio of 1:2-4.
10. The method for preparing a degradable medical liquid storage bag material according to any one of claims 1 to 9, characterized in that: The following steps are involved: PBAT resin, PLA resin, modified PBS resin, modified starch, plasticizer, and lubricant are weighed and added into a high-speed mixer and mixed for 5-15 minutes to obtain a premix. The premix is added into a twin-screw extruder for extrusion and granulation to obtain the degradable medical liquid storage bag material.